Nosocomial Oral Myiasis by Sarcophaga sp. in Turkey - Yazar, Süleyman (Yonsei University College of Medicine, 2005)
We present a case of oral myiasis in a 15-year-old boy with tuberculosis meningitis. The diagnosis was based on the visual presence of wriggling larvae about 1 cm in size and on the microscopic features of the maggots, especially those relating to stigmatic structures. The larvae were identified as third-stage larvae of Sarcophaga sp.